Pengelolaan Limbah Berbasis Masyarakat di Desa Pakam, Kabupaten Batu Bara, Sumatera Utara: Community Based Waste Management in Pakam Village, Batu Bara Regency, North Sumatra - Trimurni, Februati; Nasution, Muhammad Arifin; Aisyah, Dara; Sitepu, Yovita Sabarina; Siregar, Onan Marakali; Ginting, Wiro Oktavius; Ritonga, Siti Hazzah Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Waste management at the community level is crucial to promoting sustainable development, especially in coastal regions. The problem of household and shellfish waste being carried by ocean currents and accumulating in the environment is a concern in Pakam Village, Batu Bara Regency, North Sumatra. This state detracts from the village's aesthetic attractiveness in addition to polluting the environment. To enhance residents' ability to manage their own waste, community service projects are being implemented through the Universitas Sumatera Utara 2025 Assisted Village initiative. Technical waste processing training, stakeholder Focus Group Discussions (FGDs), the establishment of an Environmental Working Group, and the creation of local regulations in the form of Village Head Regulations (Perkades) were among the implementation strategies. Additionally, a display of processed waste products was implemented. The activities' outcomes demonstrated the development of active local institutions, a greater understanding of household waste sorting, an improvement in the community's ability to process waste into value-added products like handicrafts and calcium powder, and the creation of more practical village regulations than the Perdes. Additionally, Pakam Village was effectively linked to the Batu Bara Regency Waste Bank effort through this scheme. As a result, this service strengthened the village's institutional and regulatory foundations while also helping the community shift its perspective from viewing garbage as a problem to recognizing it as an economic resource.